2014
DOI: 10.1007/s12272-014-0454-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of SKI3246, the rhizome extract of Atractylodes japonica, on visceral hypersensitivity in experimental irritable bowel syndrome rat models

Abstract: We evaluated the effect of SKI3246, the 50% ethanol extract of the rhizome of Atractylodes japonica, on visceral hypersensitivity, which is a major characteristic feature of IBS. We used various rat models of visceral hypersensitivity to assess the visceral pain responses to colorectal distension (CRD) in comparison with conventional IBS treatments. Oral administration of SKI3246 dose-dependently and significantly attenuated the abdominal withdrawal reflex (AWR) score in a model of acetic acid-induced visceral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…In preliminary animal experiments, an extract of A. japonica rhizome (SKI3246) significantly reduced visceral pain in visceral hypersensitivity rats model using trinitrobenzene sulfonic acid (TNBS) or acetic acid. 1 The treatment also ameliorated castor oil-induced diarrhea in mice (unpublished data). These findings suggest that SKI3246 may potentially provide some relief for irritable bowel syndrome (IBS), especially when diarrhea is a principal component.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…In preliminary animal experiments, an extract of A. japonica rhizome (SKI3246) significantly reduced visceral pain in visceral hypersensitivity rats model using trinitrobenzene sulfonic acid (TNBS) or acetic acid. 1 The treatment also ameliorated castor oil-induced diarrhea in mice (unpublished data). These findings suggest that SKI3246 may potentially provide some relief for irritable bowel syndrome (IBS), especially when diarrhea is a principal component.…”
Section: Introductionmentioning
confidence: 79%
“…Although the pharmacological action of SKI3246 is not completely defined, this complex preparation has been shown its action through the neurokinin (NK) receptor antagonism, especially NK2 receptor. 1 Meanwhile, it has been known that MO displays proinflammatory activity mainly via inducing plasma extravasation, which is principally due to the release of substance P and to NK1 receptor activation. [7][8][9][10] These differences in mechanism between the 2 agents may explain in part the lack of GI motility response to SKI3246 in the MO-induced model in this study.…”
Section: Discussionmentioning
confidence: 99%
“…(1S,4S,5R,7R,10R)‐11,14‐Dihydroxy‐guai‐3‐one‐11‐ O ‐β‐D‐glucopyranoside ( 80 ), [62] (1S,4S,5S,7R,10R)‐10,11,14‐trihydroxy‐guai‐3‐one‐11‐ O ‐β‐D‐glucopyranoside ( 82 ), [62] atractyloside A ( 84 ), [62] 10‐epi‐atractyloside A ( 85 ), [62] atractyloside B ( 87 ), [62] and (1S,5R,7R,10R)‐seco‐atractylolactone‐11‐ O ‐β‐D‐glucopyranoside ( 96 ), [62] have been isolated from the rhizome of A. japonica . Atractyloside A ( 84 ), [27] (4R,5R)‐atractylmacrene A ( 98 ), [32] (4S,5S)‐Atractylmacrene A ( 99 ), [32] (1R,4R,5R)‐atractylmacrene B ( 100 ), [32] and (1S,4S,5S)‐atractylmacrene B ( 101 ) [32] guai‐10(14)‐en‐11‐ol ( 102 ), [31] have been isolated from the rhizome of A. macrocephala .…”
Section: Resultsmentioning
confidence: 99%
“…A. macrocephala [26,28,30,32–35,38,42–44,47–49,51–54,58,59] A. japonica [18,20,21,60–62] A. chinensis [16,67] A. lancea [11,64,66] A. ovata [68–71] …”
Section: Resultsmentioning
confidence: 99%
“…The other important crude drug in NJT is Atractylodes japonica . It has been reported that SKI3246 of the rhizome of Atractylodes japonica is potentially effective in treating visceral hypersensitivity in experimental rat model of irritable bowel syndrome [ 12 ]. According to the Kampo diagnosis, NJT improves interior cold, a pathological state characterized by the preponderance of yin cold or a decline in yang qi in the interior, thus tonifying the digestive system.…”
Section: Discussionmentioning
confidence: 99%